2022
DOI: 10.1136/jitc-2022-004669
|View full text |Cite
|
Sign up to set email alerts
|

Chromatin remodeling (SWI/SNF) complexes, cancer, and response to immunotherapy

Abstract: Chromatin regulation involves four subfamilies composed of ATP-dependent multifunctional protein complexes that remodel the way DNA is packaged. The SWItch/Sucrose Non-Fermentable (SWI/SNF) chromatin remodeling complex subfamily mediates nucleosome reorganization and hence activation/repression of critical genes. The SWI/SNF complex is composed of the BRG-/BRM-associated factor and Polybromo-associated BAF complexes, which in turn have multiple subunits. Significantly, ~20% of malignancies harbor alterations i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0
1

Year Published

2023
2023
2025
2025

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 101 publications
1
5
0
1
Order By: Relevance
“…PBRM1 encodes a subunit of the SWI/SNF complex, which is important in chromatin remodeling. [46] PBRM1 alterations are considered a biomarker predicting response to immunotherapy in clear cell renal cell carcinoma, [47,48] similar to what has been seen in our series. In contrast, investigation showed that PBRM1 mutations were associated with fewer immune infiltrates and lower response rates to immunotherapy.…”
Section: Discussionsupporting
confidence: 85%
“…PBRM1 encodes a subunit of the SWI/SNF complex, which is important in chromatin remodeling. [46] PBRM1 alterations are considered a biomarker predicting response to immunotherapy in clear cell renal cell carcinoma, [47,48] similar to what has been seen in our series. In contrast, investigation showed that PBRM1 mutations were associated with fewer immune infiltrates and lower response rates to immunotherapy.…”
Section: Discussionsupporting
confidence: 85%
“… 32 Other biomarkers may also predict response to immunotherapy, including but not limited to the presence of aberrant chromatin remodeling genes, T-cell repertoire, and expression of PD-1 on tumor-infiltrating lymphocytes. 33 35 …”
Section: Discussionmentioning
confidence: 99%
“…Chromatin remodeling elements are a group of proteins that redesign the way DNA architecture is bundled for the sake of facilitating the access to the condensed genomic DNA by the transcription machinery; therefore regulating gene expression. Chromatin's main purpose is thus to collect long DNA molecules into more compact, yet complicated structures (28) . In addition, nucleosomes play a main role in controlling gene expression as they prevent the binding of transcription factors, which are the key proteins in control of activating or inactivating the expression of specific genes.…”
Section: Discussionmentioning
confidence: 99%